2020
DOI: 10.1002/dta.2809
|View full text |Cite
|
Sign up to set email alerts
|

The roles of phosphatidylethanol, ethyl glucuronide, and ethyl sulfate in identifying alcohol consumption among participants in professionals health programs

Abstract: Direct alcohol biomarkers, including urinary ethyl glucuronide (EtG), urinary ethyl sulfate (EtS), and blood phosphatidylethanol (PEth), are used to monitor alcohol abstinence in individuals who are mandated to abstain. In this consecutive case series study, we examined 1000 forensic reports of participants enrolled in a professionals health program who were contractually obligated to abstain from alcohol and who underwent recovery status evaluations. We identified 52 evaluations in which urinary EtG, EtS, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Previous studies comparing EtG and EtS in the same population seem to have shown a good, even larger sensitivity for EtS compared to EtG [ 17 ]. That being said, there are also studies suggesting PEth could be more sensitive than EtS, although they have not been performed in liver transplant candidates [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing EtG and EtS in the same population seem to have shown a good, even larger sensitivity for EtS compared to EtG [ 17 ]. That being said, there are also studies suggesting PEth could be more sensitive than EtS, although they have not been performed in liver transplant candidates [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylethanol (PEth), an ethanol (EtOH) biomarker, has been frequently used and characterized in the context of groups of individuals who consume unhealthy amounts of alcohol such as those attending alcohol treatment facilities and human immunodeficiency virus (HIV) clinics. There is increasing knowledge regarding the utility of PEth in the context of community‐dwelling adults (Helander et al, 2019; Neumann et al, 2020; Nguyen et al, 2018; Reisfield et al, 2020; Schrock et al, 2017; Ulwelling and Smith, 2018). However, less is known for older adults for whom alcohol consumption can have a different, often more detrimental, impact on health (Moos et al, 2005).…”
mentioning
confidence: 99%
“…Breath testing, which is used to estimate recent alcohol consumption from the blood alcohol concentration (BAC) at the moment of sampling, or other blood‐based measures such as ethyl glucuronide and ethyl sulfate can detect very recent alcohol ingestion (Halter et al, 2008; Mastrovito and Strathmann, 2020; Neumann et al, 2020; Reisfield et al, 2020). Other common blood‐ and urine‐based measures used in a clinical setting include carbohydrate‐deficient transferrin (CDT) and serum γ‐glutamyltransferase (GGT; Litten et al, 2010; Mastrovito and Strathmann, 2020; Neumann et al, 2020; Reisfield et al, 2020). However, CDT and GGT may be influenced by other factors besides alcohol intake, including smoking, gender, age, and various diseases (Andresen‐Streichert et al, 2018; Conigrave et al, 2003; Neumann et al, 2020).…”
mentioning
confidence: 99%
See 2 more Smart Citations